2022
DOI: 10.3390/horticulturae8080745
|View full text |Cite
|
Sign up to set email alerts
|

Hurdle Approach for Control of Enzymatic Browning and Extension of Shelf Life of Fresh-Cut Leafy Vegetables Using Vacuum Precooling and Modified Atmosphere Packaging: Commercial Application

Abstract: Fresh-cut leafy vegetable has an image as a healthy, nutritious, and delicious product. However, the product still faces the challenge of quality retention and short shelf life, especially in tropical climate regions. Enzymatic browning in fresh-cut leafy vegetables is considered one of the most important attributes limiting the shelf life of the product. The hurdle approach using commercial vacuum precooling in combination with modified atmosphere packaging (MAP) as an alternative to the use of chemical prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…The combination that has been done with MAP technology in food products are vacuum treatment, ultrasound treatment, edible coating, high-voltage electrostatic field, and substances (calcium ascorbate,1methylcyclopropene) which acts as an active packaging. Several studies have reported combination treatments carried out with MAP technology; among others, combination of MAP with vacuum has been reported to be able to inhibit the enzymatic browning reaction, which can prolong the shelf life of vegetable products for 3-9 days, compared by using MAP independently 80) . The combination of MAP with ultrasound treatment is able to increase the preservation ability for meat products compared to individual treatments by inhibiting the growth of Pseudomonas and Carnobacterium bacteria and also maintaining the flavor of the meat 81) .…”
Section: Map Technology Developmentmentioning
confidence: 99%
“…The combination that has been done with MAP technology in food products are vacuum treatment, ultrasound treatment, edible coating, high-voltage electrostatic field, and substances (calcium ascorbate,1methylcyclopropene) which acts as an active packaging. Several studies have reported combination treatments carried out with MAP technology; among others, combination of MAP with vacuum has been reported to be able to inhibit the enzymatic browning reaction, which can prolong the shelf life of vegetable products for 3-9 days, compared by using MAP independently 80) . The combination of MAP with ultrasound treatment is able to increase the preservation ability for meat products compared to individual treatments by inhibiting the growth of Pseudomonas and Carnobacterium bacteria and also maintaining the flavor of the meat 81) .…”
Section: Map Technology Developmentmentioning
confidence: 99%
“…On the other hand, fruits stored at 5 • C in unsealed control bags retained their freshness up to 8 DOS, when it immediately declined to 22 • C. In the unsealed control fruits, the water loss was high, due to which the time taken to reach the fruit development phases (Rutab and Tamr) was reduced, and the fruit spoilage percentage was increased at both temperatures. It might be because the vacuum-sealed and MAP-treated dates were packaged in closed containers to prevent water loss, limiting fruit enzymatic processes and microbial activities [15,[55][56][57][58].…”
Section: Influence Of Storage Conditions On Fresh Datesmentioning
confidence: 99%